THE COMMODIFICATION OF THE WAYANG MASK AS LAKON "PANJI RENI" IN TERM OF VCD FORMAT - Wahyuningtyas, Tri (International Conference on Cultural Studies; Vol 1 (2018): Proceedings International Conference on Cultural Studies, 2018)
Wayang Topeng (a kind of a puppet show performed by someone wearing a mask) is a performance in the form of a drama displayed by dancers wearing masks who perform not only hiding their faces, but there are also goals that are more essential and symbolic, or it is not a mere performance but also related to the life patterns of the people of Malang region, East Java, Indonesia. It can be realized that the existence of Wayang Topeng has a connection with the aspects of a belief, worshipping the ancestral spirits, that can survive as a performance of art and has some values related to the formation of structures, including (1). Society, (2). Environment, (3). Social system in a community, (4). Religious system. The change in format from the stage show to the audio visual format in the VCDs format with all its adjustments led to a shift in values towards the meaning of the Wayang Topeng show from traditional to mass culture. This phenomenon is seen not by adjusting the media format, but already in the form of commodification. This paper aims at revealing the forms, processes, and powers of commodification of Wayang Topeng in “Panji Reni” story.